Vocational Education and Training and the «social question» Origin of «social aims» of vocational education and training - Bonoli, Lorenzo (Swiss Journal of Educational Research, 2018)
Vocational education and training (VET) is the most important post-compulsory educational pathway in Switzerland. The aims of VET are twofold, including an economic and a social aspect. The former includes the supply of a qualified workforce for the Swiss economy. The latter consists of supporting young people in entering the labour market and integrating successfully into society. But how can we explain the articulation of these two different aims in the Swiss VET system? When did they emerge? What were the historical conditions fostering the development of these two aims? This article will reconstruct the development and conjunction of these two aims between the end of the 19th and the beginning of the 20th century, when the origins of the current Swiss VET system were established.